Umbrella Review on Associations Between Single Nucleotide Polymorphisms and Lung Cancer Risk - Li, Xiaoying; Wu, Qijun; Zhou, Baosen; Liu, Yashu; Lv, Jiale; Chang, Qing; Zhao, Yuhong (Frontiers in Molecular Biosciences, 2021)
The aim is to comprehensively and accurately assess potential relationships between single nucleotide polymorphisms (SNP) and lung cancer (LC) risk by summarizing the evidence in systematic reviews and meta-analyses. This umbrella review was registered with the PROSPERO international prospective register of systematic reviews under registration number CRD42020204685. The PubMed, Web of Science, and Embase databases were searched to identify eligible systematic reviews and meta-analyses from inception to August 14, 2020. The evaluation of cumulative evidence was conducted for associations with nominally statistical significance based on the Venice criteria and false positive report probability (FPRP). This umbrella review finally included 120 articles of a total of 190 SNP. The median number of studies and sample size included in the meta-analyses were five (range, 3–52) and 4 389 (range, 354–256 490), respectively. A total of 85 SNP (in 218 genetic models) were nominally statistically associated with LC risk. Based on the Venice criteria and FPRP, 13 SNP (in 22 genetic models), 47 SNP (in 99 genetic models), and 55 SNP (in 94 genetic models) had strong, moderate, and weak cumulative evidence of associations with LC risk, respectively. In conclusion, this umbrella review indicated that only 13 SNP (of 11 genes and one miRNA) were strongly correlated to LC risk. These findings can serve as a general and helpful reference for further genetic studies.